2021
DOI: 10.33714/masteb.890574
|View full text |Cite
|
Sign up to set email alerts
|

The use of S-GnRHa (salmon gonadotropin releasing hormone analogue) in induced breeding and early embryonic development of Gulsha, Mystus cavasius

Abstract: The current study was carried out to optimize the dose of the synthetic hormone for induction, and to observe the embryonic and larval developmental in Gulsha, Mystus cavasius. Induced breeding was conducted by using Ovupin (S-GnRHa) hormone (each 1.5 ml vial contain 0.2 mg of an analogue of S-GnRHa) at four different doses i.e., 0.25, 0.5, 1.0-and 1.50-ml kg -1 body weight (BW) for females, and the half of these doses were applied to males. Among the applied doses, 0.5 ml kg -1 BW for female and 0.25 ml kg -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The study denoted that 29-34oC temperature was identified as the optimum range for induced breeding. Ali et al (2021) reported that the maximum fertilization rate was 83.66% and the hatching rate was 80.0 percent, which is mostly similar to this experiment where the fertilization rate was 80% and the hatching rate was recorded at…”
Section: Discussionsupporting
confidence: 86%
“…The study denoted that 29-34oC temperature was identified as the optimum range for induced breeding. Ali et al (2021) reported that the maximum fertilization rate was 83.66% and the hatching rate was 80.0 percent, which is mostly similar to this experiment where the fertilization rate was 80% and the hatching rate was recorded at…”
Section: Discussionsupporting
confidence: 86%
“…Reba's fertilized eggs (Figure 4b) demonstrate meroblastic cleavage within 30-35 min after fertilization (Figure 4c). By administering Gn-RH in Mystus cavasius, Ali et al (2021) observed the first cleavage to a 32-cell formation in 00:35-2:20h, whereas the new research ascertained the first cleavage achieved a 32-cell formation in 00:30-3:20h. At 190-210 minutes after fertilization, the morula phase was acquired (Figure 4c).…”
Section: Resultsmentioning
confidence: 86%
“…fertilization in M. cavasius. The C-shaped gastrula part (Figure 4e) starts at 6:0-6:40h post-fertilization, whereas Ali et al (2021) recorded it at 5:0-5:30h after fertilization. The winding motion of the embryo was seen in current research as it unwinds from being encircled over the yolk realm.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation